The roles of leukaemic and residual normal cells in the proliferative response of chronic lymphocytic leukaemic lymphocytes to mitogens. - Johnstone, A P (1982)
The proliferative response of lymphocytes from patients with chronic lymphocytic leukaemia (CLL) to the polyclonal activators, phytohaemagglutinin (PHA) and pokeweed mitogen (PWM) correlates inversely with the logarithm of the circulating lymphocyte concentration in vivo (P less than 0.001). This suggests that the response is due primarily to residual normal cells in the circulation. In support of this postulate, dilution of normal cells reproduced the effect and also induced a delayed response to PHA, which is found frequently with CLL lymphocytes. A combination of autoradiography and immunofluorescence microscopy identified both B and T cells in the responding population in similar proportions from both normal and CLL donors. These data demonstrate that the 3H-thymidine assay used in most mitogenic studies is not suitable alone for investigating the functional capacity of leukaemic lymphocytes in CLL and other diseases involving a gross perturbation of lymphocyte populations.